ChemInform Abstract: Integrating Metabolic Engineering and Heterogeneous Chemocatalysis: New Opportunities for Biomass to Chemicals. Issue 29 (29th June 2016) - Huo, Yanping; Zeng, Huaqiang; Zhang, Yugen
Abstract: Review: [17 refs.